2021
DOI: 10.1016/j.jare.2021.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Sleep/wake calcium dynamics, respiratory function, and ROS production in cardiac mitochondria

Abstract: Graphical abstract Sleep/wake cycle-dependent differences in molecular parameters controlling mitochondrial ability to regulate cellular levels of calcium and associated ROS production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…Mitochondria serve as the primary organelles for reactive oxygen species (ROS) production in cardiomyocytes [ 7 ]. Cardiac aging is accompanied by a decline in mitochondrial function, accumulation of dysfunctional mitochondria, increased ROS production, and dysregulated mitochondrial quality control [ 8 , 9 ]. Damaged mitochondria cannot be easily cleared away via cell division, given their insufficient ability to proliferate and dilute damaged mitochondria through cell division.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria serve as the primary organelles for reactive oxygen species (ROS) production in cardiomyocytes [ 7 ]. Cardiac aging is accompanied by a decline in mitochondrial function, accumulation of dysfunctional mitochondria, increased ROS production, and dysregulated mitochondrial quality control [ 8 , 9 ]. Damaged mitochondria cannot be easily cleared away via cell division, given their insufficient ability to proliferate and dilute damaged mitochondria through cell division.…”
Section: Introductionmentioning
confidence: 99%
“…For example, nuclear factor-erythroid 2-related factor 2 (NRF2) serves as a redox-responsive factor and mediates ROS elimination, 256 while downregulation of NRF2 is observed in elderly individuals. As expected, reduced ROS production or the oxidized form of glutathione (GSSG) disposition ameliorates cardiac aging, 257,258 supporting the concept that ROS derived by mitochondria are harmful to aging hearts. Recently, the correlation between ROS with cardiac aging is reported in some preclinical studies.…”
Section: Mitochondrial Ros and Mtdnamentioning
confidence: 54%
“…More recent evidence indicates that many cation channels can be regulated over daily time ( Abdel-Rahman et al, 2021 ). We thus wondered whether the protein levels of Letm1 might change across the day.…”
Section: Resultsmentioning
confidence: 99%
“…This observation raises the question of whether internal clocks also set the pace of mitochondrial solute carriers and H + -cation exchangers, as these are critical for chemiosmotic processes. In this context, a correlative study between diurnal fluctuation of cardiac OXPHOS and Ca 2+ dynamics has shown increased activity of the mitochondrial Na + /Ca 2+ exchanger and Ca 2+ transporters, as well as a higher mitochondrial Ca 2+ retention capacity at night than in the day, and attributed the increased cardiac daytime vulnerability to reduced daytime mitochondrial Ca 2+ dynamics ( Abdel-Rahman et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%